2018
DOI: 10.1007/s10714-018-2474-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonequatorial circular orbits of spinning particles in the Schwarzschild–de Sitter background

Abstract: In this paper analytical solutions of the Mathisson-Papapetrou equations that describe nonequatorial circular orbits of a spinning particle in the Schwarzschild-de Sitter background are studied, and the role of the cosmological constant is emphasized. It is shown that generally speaking a highly relativistic velocity of the particle is a necessary condition of motion along this type of orbits, with an exception of orbits locating close to the position of the static equilibrium, where low velocities are possibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The quadratic equation for the orbital frequency of an extended, spinning, test body, in the Schwarzschild black hole limit is reduced to: (24) which coincides with the expression presented in [31], when the Kerr parameter is set to zero. The solutions of such an equation and the behaviour of its discriminant, have been thoroughly examined by numerous authors and in more general contexts (a = 0).…”
Section: Tulzcyjew-dixon Sscsupporting
confidence: 55%
See 1 more Smart Citation
“…The quadratic equation for the orbital frequency of an extended, spinning, test body, in the Schwarzschild black hole limit is reduced to: (24) which coincides with the expression presented in [31], when the Kerr parameter is set to zero. The solutions of such an equation and the behaviour of its discriminant, have been thoroughly examined by numerous authors and in more general contexts (a = 0).…”
Section: Tulzcyjew-dixon Sscsupporting
confidence: 55%
“…These helices were considered for long time to be unphysical until their nature was interpreted in [22]. This SSC is quite popular in analytical works [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is necessary to study the influence of the spin-gravity coupling on the particle trajectories, especially when its velocity is very high. Various cases of the essentially nongeodesic orbits of a highly relativistic spinning particle in Schwarzschild's field, which follows from the MP equations, are investigated in [16][17][18][19][20][21]. In particular, it is shown that, due to the strong action of the highly relativistic spin-gravity coupling, there are circular orbits of a spinning particle in the Schwarzschild field which significantly differ from the circular orbits of a spinless particle in this field.…”
Section: Role Of the Very High Particle Velocitymentioning
confidence: 99%
“…The motion of the spinning test particle in the Horndeski theory was also investigated in [61]. Some works have addressed the motion of a spinning test particle with non-zero cosmological constant in Schwarzschild and Kerr-de Sitter spacetimes [62][63][64][65], for which the equilibrium conditions and nonequatorial circular orbits were investigated.…”
Section: Introductionmentioning
confidence: 99%